Pelatihan Pengembangan Sumber Daya Manusia (SDM) Melalui Peran Komunitas Jendela Literasi (Jeli) Dalam Meningkatkan Soft Dan Hard Skill Di Kelurahan Penaraga Kecamatan Raba Kota Bima - Lubis Hermanto; Ariani Rosadi; Mas’ud Mas’ud; Syamsuddin Syamsuddin (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
Bima City as one of the autonomous regions in its development began to establish a non-formal education center in Bima City. The scope and variety of current activities ranging from Life Skills (Education to Life Skills) and courses, so today's educational activities cannot be underestimated, which for some people is considered only oriented to awarding equality certificates to people who do not have time or are forced to leave formal education bench. The methods for implementing these activities include: varied lectures, demonstrations, and exercises.The results of this training will be useful for community members, the teaching and learning process will be more interesting with the use of more varied learning media. In addition, the existence of community member development training through institutional strengthening will increase the skills of community members in developing creativity so that it will support and create superior members so that they are able to create ideas and innovations in the era of global competition as it is today.